The Effect of Product Quality, Brand Image, E-Word of Mouth, Free Shipping Promo, and Online Customer Rating on Purchasing Decisions for Nocturn.Co Online Products - Aziz, Geovanni Al; Astuti, Herni Justiana; Haryanto, Totok; Bagis, Fatmah (International Journal of Business and Applied Economics, 2025)
This research had the aim to find out about the effect of product quality, brand image, e-word of mouth, free shipping promo, as well as online customer rating on purchasing decisions. Structural Equation Modeling (SEM) was implemented as the technique for data analysis, with the use of SmartPLS version 4.0 software. The population consists of Nocturn.co customers who have made a purchase. Roscoe method was used as the sampling technique, which resulted in a total of 103 respondents. The findings revealed that brand image, free shipping promo, as well as online customer rating positively and significantly affect purchasing decisions, whereas product quality and electronic word of mouth do not affect purchasing decisions.